2010
DOI: 10.1007/s00284-010-9719-x
|View full text |Cite
|
Sign up to set email alerts
|

Field Evidence for the Potential of Rhodobacter capsulatus as Biofertilizer for Flooded Rice

Abstract: In a previous study, we evaluated the effects of inoculating rice plants with the phototrophic purple nonsulfur bacterium Rhodobacter capsulatus (Rc) on growth and yield of rice in pots and lysimeter experiments and the results obtained have been highly encouraging. In this study, we carried out two field experiments: one in the experimental farm of the Faculty of Agriculture, Fayoum University, and the second in a farmer's field in Kafr El-sheikh, to assess the effects of Rc on growth and yield of rice in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…with brown colonies (Nakayama et al 2006). These genera are typically photoheterotrophic PNSB found in paddy soil (Harada et al 2003b;Lakshmi et al 2009;Gamal-Eldin and Elbanna 2011) and they can use various fatty acids (Kim et al 2004). However, in this work we have not yet identified the isolated PNSB except for their different coloured colonies; red colonies like with rod shapped cells 75%, brown colonies with rod shapped cells 24%, and dark-brown colonies with spiral shape cells 1%.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…with brown colonies (Nakayama et al 2006). These genera are typically photoheterotrophic PNSB found in paddy soil (Harada et al 2003b;Lakshmi et al 2009;Gamal-Eldin and Elbanna 2011) and they can use various fatty acids (Kim et al 2004). However, in this work we have not yet identified the isolated PNSB except for their different coloured colonies; red colonies like with rod shapped cells 75%, brown colonies with rod shapped cells 24%, and dark-brown colonies with spiral shape cells 1%.…”
Section: Discussionmentioning
confidence: 76%
“…In addition to using various organic compounds in wastewater treatment (Takeno et al 2005) they can produce H2 (Suwansaard et al 2009), indole-3-acetic acid (IAA) and 5-aminolevulinic (ALA) (Koh and Song, 2007) and many can fix N2 gas (Harada et al 2005). Therefore, PNSB have been considered to be one of 'Natures Biofertilizers' and they also have the potential to reduce CH4 emission by growing out competing methanogenic bacteria in the light (Harada et al 2003a;Gamal-Eldin and Elbanna, 2011). Recently 'organic' agriculture is becoming popular in Thailand and thereby PNSB have already been sold as commercial biofertilizers for use in paddy fields and also for shrimp cultivation although they are very expensive as there is no competition.…”
Section: Introductionmentioning
confidence: 98%
“…These properties make them ideal for wastewater bioremediation [10]. Several strains of PNSB are also known to have plant growth promoting abilities in terms of nitrogen fixation [11], phosphate solubilization, and production of phytohormones such as indole-3-acetic acid and 5-aminolevulinic (ALA) [12]. The most common genera are Rhodobacter and Rhodopseudomonas , detected in 73% and 80% of the samples, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…), a typical phytohormone regulating various developmental and physiological processes in plants (Lee et al . ; Gamal‐Eldin and Elbanna ).…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al (2011) studied the heterotrophic metabolism of Rubrivivax gelatinosus in the fish industry effluent and found that the bacteria could remove organic pollutants in the wastewater. In addition, PNSB could secrete indole-3-acetic acid (IAA) in the presence of L-tryptophan (Mujahid et al 2010), a typical phytohormone regulating various developmental and physiological processes in plants (Lee et al 2008;Gamal-Eldin and Elbanna 2011).…”
Section: Introductionmentioning
confidence: 99%